Perceptions, Barriers, and Challenges of Healthcare Providers in Adolescent Pregnancy Prevention Services: A Scoping Review - Najma Fitya Afifa; Shaluhiyah, Zahroh; Indraswari, Ratih (Jurnal Promkes: The Indonesian Journal of Health Promotion and Health Education, 2025)
Background: Adolescent pregnancy remains a significant global health problem, this is because related with increased risks to maternal and child health, psychology, as well as its socioeconomic. Efforts to provided quality adolescent sexual and reproductive health (ASRH) services as pregnancy prevention still need an understanding from the perspective of healthcare providers. Objective: This review aimed to explored the perceptions, barriers and challenges faced healthcare providers in provided ASRH services as an effort to prevent and reduce cases of adolescent pregnancy. Methods: The procedures began with a search on Scopus, ScienceDirect, dan EBSCOhost databases studies published between 2020 until 2025 using Arksey and O'Malley's framework and the PRISMA-ScR checklist. Based on the search results, a total of 11 peer-reviewed studies met stringent inclusion criteria, focusing perspective of healthcare providers. Results: This review was done of 11 articles that were screened and analyzed out of 337 articles. The articles come from United States of America, Uganda, South Africa, Tanzania, Lebanon, Haiti, Zambia, and Kenya, 9 articles utilizes qualitative designs and 2 articles utilizes cross-sectional designs. Conclusion: This review providing an overview variations in perceptions, barriers and challenges from perspective if healthcare providers in various countries on implementation of ASRH services and indicates need a holistic approach not only to adolescents as service recipients, but also to healthcare providers as key actors.